Answer:
8
Step-by-step explanation:
It is in the one's place, so it is just 8x1, which is 8
Answer:
35/3
Step-by-step explanation:
![\frac{x+6 + 6x+2+x+6}{3} =4x-7](https://tex.z-dn.net/?f=%5Cfrac%7Bx%2B6%20%2B%206x%2B2%2Bx%2B6%7D%7B3%7D%20%3D4x-7)
Simplify to get
9x+14=3(4x-7)
35=3x
x=35/3 or 11.66
The value of x, y and z from the system of equation are -1, -8 and 5 respectively.
Data;
- -2x + 6y + 3z = -31
- -3y + 7z = 59
- 2z = 10
<h3>System of Equation</h3>
To solve this problem, we have to solve the system of equation using substitution method.
From equation (iii)
![2z = 10\\z = 5](https://tex.z-dn.net/?f=2z%20%3D%2010%5C%5Cz%20%3D%205)
let us substitute the value of z into equation (ii)
![-3y + 7z = 59\\z = 5\\-3y + 7(5) = 59\\-3y + 35 = 59\\-3y = 59 - 35\\-3y = 24\\y = -8](https://tex.z-dn.net/?f=-3y%20%2B%207z%20%3D%2059%5C%5Cz%20%3D%205%5C%5C-3y%20%2B%207%285%29%20%3D%2059%5C%5C-3y%20%2B%2035%20%3D%2059%5C%5C-3y%20%3D%2059%20-%2035%5C%5C-3y%20%3D%2024%5C%5Cy%20%3D%20-8)
Let's substitute the value of x and y into equation (i)
![-2x + 6y + 3z = -31\\y = -8, z = 5\\-2x + 6(-8) + 3(5) = -31\\-2x - 48 + 15 = -31\\-2x - 33 = -31\\-2x = -31 + 33\\-2x = 2\\x = -1](https://tex.z-dn.net/?f=-2x%20%2B%206y%20%2B%203z%20%3D%20-31%5C%5Cy%20%3D%20-8%2C%20z%20%3D%205%5C%5C-2x%20%2B%206%28-8%29%20%2B%203%285%29%20%3D%20-31%5C%5C-2x%20-%2048%20%2B%2015%20%3D%20-31%5C%5C-2x%20-%2033%20%3D%20-31%5C%5C-2x%20%3D%20-31%20%2B%2033%5C%5C-2x%20%3D%202%5C%5Cx%20%3D%20-1)
From the calculation above, the value of x, y and z are -1, -8 and 5 respectively.
Learn more on system of equations here;
brainly.com/question/14323743
7:14:21
Add 1,2,3 = 6
Divide 6 by 42=7
Then 7x1=7
7x2=14
7x3=21
Using simple interest, it is found that $13,872 was loaned at 9%.
<h3>Simple Interest</h3>
The amount of money after t years in simple interest is modeled by:
![A(t) = P(1 + rt)](https://tex.z-dn.net/?f=A%28t%29%20%3D%20P%281%20%2B%20rt%29)
In which:
- r is the interest rate, as a decimal.
The interest earned is:
![I(t) = Prt](https://tex.z-dn.net/?f=I%28t%29%20%3D%20Prt)
A bank loaned out $14000, in two parts, hence:
![P_2 = 14000 - P_1](https://tex.z-dn.net/?f=P_2%20%3D%2014000%20-%20P_1)
Part of it at the rate of 9% per year and the rest at 17% per year, hence:
![r_1 = 0.09, r_2 = 0.17](https://tex.z-dn.net/?f=r_1%20%3D%200.09%2C%20r_2%20%3D%200.17)
The interest received in one year totaled $2000, hence:
![I_2 = 2000 - I_1](https://tex.z-dn.net/?f=I_2%20%3D%202000%20-%20I_1)
Then:
![I_1 = 0.09P_1](https://tex.z-dn.net/?f=I_1%20%3D%200.09P_1)
![I_2 = 0.17I_2](https://tex.z-dn.net/?f=I_2%20%3D%200.17I_2)
![14000 - P_1 = 0.17(2000 - I_1)](https://tex.z-dn.net/?f=14000%20-%20P_1%20%3D%200.17%282000%20-%20I_1%29)
Isolating
as a function of
, then we can replace on the equation for the first interest.
![14000 - P_1 = 340 - 0.17I_1](https://tex.z-dn.net/?f=14000%20-%20P_1%20%3D%20340%20-%200.17I_1)
![0.17I_1 = -13660 + P_1](https://tex.z-dn.net/?f=0.17I_1%20%3D%20-13660%20%2B%20P_1)
![I_1 = \frac{P_1 - 13660}{0.17}](https://tex.z-dn.net/?f=I_1%20%3D%20%5Cfrac%7BP_1%20-%2013660%7D%7B0.17%7D)
Then:
![I_1 = 0.09P_1](https://tex.z-dn.net/?f=I_1%20%3D%200.09P_1)
![\frac{P_1 - 13660}{0.17} = 0.09P_1](https://tex.z-dn.net/?f=%5Cfrac%7BP_1%20-%2013660%7D%7B0.17%7D%20%3D%200.09P_1)
![P_1 - 13660 = 0.0153P_1](https://tex.z-dn.net/?f=P_1%20-%2013660%20%3D%200.0153P_1)
![0.9847P_1 = 13660](https://tex.z-dn.net/?f=0.9847P_1%20%3D%2013660)
![P_1 = \frac{13660}{0.9847}](https://tex.z-dn.net/?f=P_1%20%3D%20%5Cfrac%7B13660%7D%7B0.9847%7D)
![P_1 = 13872](https://tex.z-dn.net/?f=P_1%20%3D%2013872)
$13,872 was loaned at 9%.
To learn more about simple interest, you can take a look at brainly.com/question/25296782